Third-order critical family therapy: rethinking psychopathology and psychotherapy - Raúl Medina Centeno (Interacciones)
Background: The focus of third-order critical family therapy is to raise awareness of the systems of systems – structural, socioeconomic and cultural contexts– that organize lifestyles that interfere with health. This clinical proposal integrates systemic wisdom with social theories, and in particular delves into a sociocultural theory of the human mind, power and emotions, a set of concepts from which indignant love, solidarity dialogue, critical honesty emerge, as the axes from which clinical work is woven. The ultimate goal is for the family to restore critical solidarity dialogue and empower themselves in their well-being. Method: Our study is narrative. Conclusion: This clinical proposal leads to re-thinking psychopathology not as an individual or biological problem, but as a resistance to those contexts of belonging that excludes and mistreats, and therefore to diagnosis as an active organized social framework. And on the other hand, also to psychotherapy and psychotherapist who must always be critically attentive to explain the androcentrist, classist and Eurocentric privileges of clinical theory and practice, to become health professionals with a social, human, political and ethical perspective.